Fine structure of a virus-encoded helper T-cell epitope expressed on FBL-3 tumor cells. - Shimizu, T (1994)
Antigen peptide fn20 representing Friend murine leukemia virus env122-141 (DEPLTSLTPRCNTAWNRLKL) is recognized by two independent Friend virus-induced, FBL-3 tumor-specific helper T-cell (Th) clones. We isolated more Th clones from mice immunized with fn20 peptide. We examined the fine structure of the peptide required to activate a large group of fn20-specific Th clones. A systematic analysis of peptides of decreasing lengths eliciting Th proliferation defined the minimum core length as 13 amino acids (LTSLTPRCNTAWN). Functional proliferation and competition assays with variant peptides with alanine substitutions permitted the assignment of five peptide residues in two major histocompatibility complex-interacting and three T-cell-receptor-interacting sites. Th clones were different in their reactivities toward peptides of various lengths and the variant peptides.